Effectiveness of working memory on visual-spatial working memory performance of pre-school children with learning problem at risk - Bayat Shahbazi, Farzaneh; Arjmandnia, Ali Akbar; Nemati, Reyhaneh (Majallah-i ravānshināsī va ravānʹpizishkī-i shinākht = Shenakht journal of psychology and psychiatry, 2022)
Introduction: Specific learning difficulties are the existence of disorder in one or more of the basic psychological processes which play a role in the process of understanding and using spoken or written language. Aim: The current study aimed to investigate the effect of working memory intervention on visual-spatial working memory performance among the preschool children at risk of learning disabilities. Method: This study was a quasi-experimental study including pretest and posttest design with a control group. The statistical population comprised all children who were studying in preschool centers and kindergartens (2016-2017) in Tehran (District 14). A sample of 20 preschool students who were selected through purposive sampling participated in this study. They were randomly divided into two experimental and control groups (10 participants in each group). The experimental group participated in working memory program to 60-minute 12 sessions during the three months. In order to measure the performance of working memory, the working memory subset of IQ scale, Tehran-Stanford-Binet test and N-Back test were used. The data were analyzed by SPSS-22 and t-Test. Results: The mean and standard deviation of the subjects age are 6.2 and 0.45, respectively. The results showed that the working memory intervention caused the improvement on visual-spatial working memory performance of children (P<0.001). Conclusion: Considering the findings of the present study, it seems that visual-spatial working memory intervention can improve the working memory of preschool children and it can be used to enhance the visual-spatial working memory function of children and prevent the learning problems.